TOOLS OF ANTI-CRISIS MANAGEMENT AT AN ENTERPRISE UNDER UNCERTAINTY - A. I. Podgornaya (Russian Journal of Economics and Law)
The article investigates the issues of implementation of the modern tools of anti-crisis management of an enterprise. The author grounds the approach to the tasks of modern anti-crisis management as a key factor of forming of self-developing enterprises. Thearticle views the transformation of anti-crisis management system from the point of view of systemic approach to an enterprise stability.